COMPARISON OF TWO DIFFERENT DOSES OF HYPERBARIC BUPIVACAINE IN SEGMENTAL SPINAL ANESTHESIA FOR LAPAROSCOPIC CHOLECYSTECTOMY - BHALAVI, MONA; SHAKYA, MANJU LATA; BHUPESH KHUSHRAM; KISHOR UIKEY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Thoracic segmental anesthesia, as opposed to general anesthesia (GA), is increasingly preferred by anesthesiologists for laparoscopic cholecystectomy in both sick and healthy patients because it provides favorable operating conditions, a faster block time, and better hemodynamic stability. This study compared the efficacy of two different dosages of hyperbaric bupivacaine administered during segmental spinal anesthesia. Methods: In the current study, 54 American society of anesthesiologists Grade 1 and two patients undergoing elective laparoscopic cholecystectomy were randomly assigned to either Group A, which used 1.5 mL of hyperbaric bupivacaine mixed with 0.5 mL of fentanyl, or Group B, which used 2 mL of hyperbaric bupivacaine mixed with 0.5 mL of fentanyl. Primary objectives were to determine the onset and duration of the sensory and motor block, as well as height of sensory block. Determining the hemodynamic factors and complications were the secondary objectives. The mean, standard deviation, independent t test, Chi-square test, and p-value were used to calculate the data. p<0.05 was regarded as significant. Only some drugs were routinely given to the patient to manage their anxiety, discomfort, shoulder tip pain, etc., before, during, or after operation. Results: Onset of analgesia occurred in 2.5 min for Group A and 2.2 min for Group B. The sensory and motor blocks in Group B lasted longer than in Group A, but the differences were not statistically significant. No patients in either group reported any neurological complications, and there were no discernible differences between the two groups’ hemodynamic and respiratory dysfunctions. Despite some patients experiencing minor discomfort that was easily controlled by midazolam and ketamine in small doses, none of them required the conversion to GA. In two instances, Mephentermine was required to treat hypotension. In every patient, recovery went without a side effect. Conclusion: According to this preliminary study, laparoscopic surgery on healthy people can be performed with segmental spinal anesthesia using low doses of bupivacaine that is just as effective as high doses and present fewer complications.